Within the Walls of Collemaggio. Psychiatric Photography between Use and Abuse (Itinera, 2019)
This research is the first of its kind in addressing the story and the internal affairs of the former Psychiatric hospital of Collemaggio, Aquila. A few years ago a collection of pictures of the patients was found within the walls of the Hospital. This study aims at analysing the different iconography that the pictures represent, to put them inside the historical evolution of psychiatric photography. This was made possible by the papers collected by the Association 180 Amici-L’Aquila. The second objective of this study is the iconographic comparison between the healthy state of the patients before and after the closure of the Hospital.